1931
DOI: 10.1084/jem.54.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Psittacosis

Abstract: 1. The virus of psittacosis is present in the nasal secretions, feces, blood, spleen, and liver of an infected parrot. 2. Parrots are susceptible to intraoral, intranasal, or intramuscular inoculations of the virus. 3. The most constant pathological changes produced by psittacosis in parrots occur in the spleen and liver. The lesions exhibited in the latter organ consist of areas of necrotic liver cells and damage to bile ducts. In no instance, in our experience, were lesions obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1936
1936
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Similar findings have been reported previously (Rivers et al 1931;Surman et al 1974;Hashimoto et al 1985;Hirai, 1985;Moore and Petrak, 1985). In the present study, focal necrosis with associated basophilic intracytoplasmic inclusion was also observed in the adrenal gland.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Similar findings have been reported previously (Rivers et al 1931;Surman et al 1974;Hashimoto et al 1985;Hirai, 1985;Moore and Petrak, 1985). In the present study, focal necrosis with associated basophilic intracytoplasmic inclusion was also observed in the adrenal gland.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that this phenomenon is probably associated with dissemination of chlamydial organisms within the host. Cytoplasmic inclusion bodies of variable in size on smear preparations from the affected tissues are pathognomonic for chlamydiosis (Rivers et al, 1931;Beasley e? al, 1959Beasley e?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations